Coherence in qualitative research - vaismoradi, Mojtaba; Salsal, Dr mahvash (Advances in Nursing & Midwifery, 2011)
Coherence in qualitative research Vaismoradi, M.1 (MSN); Salsali, M.2* (PhD) 1. PhD candidate, Faculty of Nursing and Midwifery, Tehran University of Medical Sciences, Tehran, Iran. 2. Professor, Faculty of Nursing and Midwifery, Tehran University of Medical Sciences, Tehran, Iran. Abstract Background and aim Coherence describes the fit between the aim, the philosophical perspective adopted, and the researcher role in the study as well as the methods of investigation, analysis and evaluation undertaken by the researcher. This review study aimed to elucidate one of the important qualitative methodology issues entitled coherence, which is usually undermined during a qualitative study. Materials and methods The authors logged on to some general and specialized search engines as well as conducted a library research in healthcare and social science textbooks to perform an in-depth study regarding coherence in qualitative research. The search resulted in 95 articles and 20 textbooks. In spite of the importance of coherence in qualitative methodology, 23 articles and 7 textbooks had more content regarding the subject, which were employed to write this paper. Findings The gathered data were classified into 4 categories: the definition of coherence; the proofs for incoherence in qualitative methodology; the causes of incoherence; and, finally, the strategies for coherence improvement in qualitative methodology. Conclusion Different factors may cause incoherence in qualitative research, which reduce the rigor and credibility of it. In addition, in the long run, it results in uncontrolled methodological diversities and inability to define criteria to judge qualitative research reports. Keywords: Coherence, Rigor, Qualitative methodology. *Corresponding Author: Mahvash, Salsali. Professor, Faculty of Nursing and Midwifery, Tehran University of Medical Sciences, Tehran, Iran. E-mail: m_salsali@hotmail.com